Education that Matters - Westheimer, Joel (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
Forty years ago, the Summer Olympics were being held in Montreal, the CN Tower opened to the public, and Canadians were introduced to a bite-sized piece of fried dough called a Timbit. “I Write the Songs” by Barry Manilow hit No. 1 on the music charts, and Steve Wozniak and Steve Jobs started a small company called Apple Computer in the garage of Jobs’s parents’ house in Cupertino, California. The same year, the Canadian Society for the Study of Education (CSSE), Canada’s premier association for professors, students, and researchers in education, published the first issue (January 1976) of the Canadian Journal of Education (CJE). It was distributed free to all CSSE members (non-members could buy one for $2!). In his opening editorial, founding editor Ronald G. Ragsdale expressed his hope that Canadian educators would use CJE as a “national forum for the exchange of ideas…a written record of the issues in education of concern to Canadians” (Ragsdale, 1976, p. 1).